GALC Triggers Tumorigenicity of Colorectal Cancer via Senescent Fibroblasts - Yang, Mengdi; Jiang, Zhiyuan; Yao, Guangyu; Wang, Zhiyu; Sun, Jing; Qin, Huanlong; Zhao, Hui (Frontiers in Oncology, 2020)
Colorectal cancer (CRC)-associated senescent fibroblasts may play a crucial role in tumor progression, but the mechanism remains unclear. In order to solve this complicated problem, we randomly collected sixteen patients with CRC, who had been treated with oxaliplatin and capecitabine (XELOX). Hematoxylin-eosin (HE) staining revealed that the Tumor-stroma ratio (TSR) of CRC was affected by XELOX treatment. Immunohistochemistry (IHC) and senescence‐associated β‐galactosidase (SAβG) staining were used to verify a stable model of senescent fibroblasts. IHC analysis showed that high expression levels of galactosylceramidase (GALC) and significant senescence‐associated β‐galactosidase (SAβG) staining were associated with CRC patient survival. We observed that fibroblasts overexpressing GALC underwent cell cycle arrest. Changes in cell morphology and cell cycle characteristics were accompanied by the upregulation of the p16, p21, and p53 gene, and the downregulation of hTERT expression. In a co-culture system, fibroblasts overexpressing GALC significantly increased the proliferation of CRC cells. Transmission Electron Microscopy (TEM) analysis confirmed that GALC overexpression fibroblasts co-cultured with CRC caused changes in CRC cell morphology. The aging fibroblast co-culture group (70%) had a higher migration ability. In vivo experiments and transcriptomics analysis were performed to verify the effect of senescent fibroblasts on tumor formation and to identify the potential mechanisms for the above results. We found that a high expression of ATF3 was related to good survival rates. However, a high expression of KIAA0907 was bad for survival rates (p<0.05). The knockdown of ATF3 can promote cell proliferation, migration, and clonogenic assays, while down-regulation of KIAA0907 inhibits cell proliferation, migration, and clonogenic assays. The results demonstrate that senescent fibroblasts with a high level of GALC regulated several aspects of the tumor growth process, including migration and invasion.